Life story work for children and young people with care experience: A scoping review. (December 2020) - Hammond, Simon P.; Young, Julie; Duddy, Claire
This scoping review was undertaken to provide an overview of peer-reviewed empirical evidence concerning the undertaking of Life Story Work (LSW) with children and young people with care experience (CYPCE). Our search identified 1, 336 potentially relevant publications. Of these, 24 empirical studies met our inclusion criteria and examined a wide range of practices in different countries. Using a thematic approach, key findings and characteristics related to current conceptualizations of LSW are explored and knowledge gaps identified. Our review shows that predominantly small-scale qualitative studies have been undertaken. These studies typically reported participants' experiences and perspectives on pre-existing LSW practices (17 articles), or evaluations of innovative practices (7 articles). However, both lacked efficacy data. We identified numerous LSW practices that were consistently identified as providing "high-quality" experiences: young person-led approaches; consistent support to access and process personal information, including chronological facts, reasons for care entry and beyond; the use of artifacts; and assistance/training for carers supporting LSW. The included studies also identified practices that undermined LSW: rushed, incomplete accounts, using insensitive language that failed to include different voices from a young person's past. The discussion appraises the findings through a critical lens and concludes that LSW is a clear priority for all and represents an intervention that has potential to help the unaddressed mental health needs of CYPCE. Unfortunately, without better evidence on how this intervention works best, for whom, over what period, and at what cost, practice cannot move forward. This paper challenges all stakeholders to realize this potential.